Gozdna tla Mestne občine Ljubljana - Urbančič, Mihej (Gozdarski vestnik, 2010)
With regard to the digital 1 : 25.000 pedologic maps and bases of pedologic data, the buffer capabilities of forest soil were determined and carbon supplies in the soil of the Municipality of Ljubljana (MOL) were preliminarilyassessed. The studied forest soil comprise 11.650 ha or 42 % of the MOL area and contain 58 % of the total of over 3.5 M tons of carbon in allsoil in the MOL. Over 70 % of forest areas are situated on non-carbonate rocks poor with bases where diverse sorts of dystric soil have developed.
Keywords: gozdna tla; gozdovi; pedologija; Ljubljana City Municipality; Mestna občina Ljubljana; Ljubljana